Estudo das relações entre a atitude de perdoar ofensas interpessoais e os esquemas iniciais desadaptativos - Santana, Rodrigo Gomes (2011)
This research was designed to examine the relationship between the willingness to forgive in specific situations and intensity of Early Maladaptive Schemas in a nonclinical sample of adults. Forty-one people participated in the survey, with an average age of 27.8 years. Were used three instruments: the Enright Forgiveness Inventory (EFI), the Crowne-Marlowe Social Desirability Scale and the Young Schema Questionnaire (short version). After application of the measures, statistical procedures were applied. In terms of results related to EFI, the same way in other studies that used this scale, were found positive correlations of the subscales of behavior, cognition and affection among themselves and with the total score of EFI, as well as with the 1-Item Forgiveness Scale an independent measure to evaluate how much the individual has forgiven the offender, in a complete mode. The results also showed that the EFI total score and the 1-Item Forgiveness Scale correlated positively, while the social desirability scale didn t show significant correlations with any of the two measures. Concerning the intensity of the offense, there was a negative correlation of this variable with measures of forgiveness, indicating that the degree of forgiveness was less the greater the perceived intensity of injury. With respect to the intensity of forgiveness, the average degree of forgiveness of the participants was 266 points a score that ranges from 60 (low degree of forgiveness) to 360 (high degree of forgiveness) and over half of the sample (61%, n = 25) reported levels of forgiveness higher than average. In terms of degrees of forgiveness measured by subscales of the EFI, the results showed that sample expressed more intensely the cognitive forgiveness (M = 96.8). The degree of affective forgiveness (M = 81.3) remained significantly lower than the degree of behavioral forgiveness (M = 88.2) and cognitive forgiveness, indicating that it was harder to participants offer the emotional forgiveness. Finally, considering the main objective of this research, the results showed negative correlations between the measure of forgiveness used as a criterion variable (1-Item Forgiveness Scale) and four of the five domains of schemes proposed by Young, to wit: disconnection and rejection (ρ = -0.534, p <0.05), impaired autonomy and performance (ρ = -0.440, p < 0.05), other-directedness (ρ = -0.371, p < 0.05) and finally, the impaired limits domain (ρ = -0.472, p < 0.01). Thus, the probability of the participants forgive their offenders has decreased as a function of the magnitude of the participant's domains and their schemes. The results observed in this study expands the current knowledge about the process of forgiveness, as well as about its interface with the cognitive structures called schemas, which have an important role in the organization of the personality, from the therapeutic point of view in cognitive approaches.